1995
DOI: 10.1017/s0950268800051906
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and antibiotic susceptibility ofVibrio choleraenon-O1

Abstract: SUMMARYA collection of 64 clinical and environmental Vibrio cholerae non-01 strains isolated in Asia and Peru were characterized by molecular methods and antibiotic susceptibility testing. All strains were resistant to at least 1 and 80% were resistant to two or more antibiotics. Several strains showed multiple antibiotic resistance ( > three antibiotics). Plasmids most often of low molecular weight were found in 21/64 (33%) strains. The presence of plasmids did not correlate with antibiotic resistance or infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…h Non-O1, non-O139 strains isolated from patients in Thailand (18). i O1 strains isolated from patients in Samutsakorn, Thailand (17).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…h Non-O1, non-O139 strains isolated from patients in Thailand (18). i O1 strains isolated from patients in Samutsakorn, Thailand (17).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 176 V. cholerae strains, mainly isolated in Thailand, were tested for the presence and contents of class 1 integrons. The strain collection was selected from a large number of V. cholerae strains studied previously for various phenotypic and genotypic characteristics (5,14,(16)(17)(18)(19). The majority of strains were sulfonamide resistant, but strains showing intermediate resistance or susceptibility to sulfonamides were also studied.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies performed in Tanzania and Bangladesh reported strains of V. cholerae with plasmid-mediated resistance to a wide range of antibiotics (Mhalu et al 1979, Threlfall & Rowe 1982. Dalsgaard et al (1995) reported that of 23 environmental V. cholerae non-O1 strains, 78.3% exhibited resistance to tetracycline and 8.7% were resistant to ampicillin and chloramphenicol. These results differ from the results of the present study.…”
Section: Discussionmentioning
confidence: 99%